DIRECTIONS OF THE HUMANISTIC EDUCATIONAL PROCESS IN CORRESPONDENCE EDUCATION SYSTEM (Pedagogy of Higher and Secondary Education, 2008)
The aim of this article is to determine possible problems and priority tendencies of forming human behaver system for student of distance reportment.